Seaweed Species Diversity with Relation to Hydrological Parameters from Veraval and Sikka Coast, Gujarat, India - Pathak, Shivani; Bhatt, A. J.; Vandarwala, U. G.; U. D., Vyas; Gautam, Priyanka (International Journal of Bio-resource and Stress Management, 2021)
The aim of the present investigation focused on a different group of seaweeds observed from Veraval and Sikka coast, Gujarat from September 2019 to February 2020, to understand their seaweeds diversity with subsequent analysis of relevant hydrological parameters. Seaweed diversity at Veraval and Sikka coasts has been studied for six months the using belt transect method. Some of the seaweeds are present throughout the year but most of the seaweeds are found at a specific climate. During the present study, the seawater temperature was ranging from 26.80 to 33˚C. The pattern of pH variation was similar in both areas but values varied considerably ranging from 7.7 to 8.32. Salinity was ranging from 32.4 to 35.67 ppt. The dissolved oxygen concentration varies from 5.64 to 7.55 ppm. In this study, the correlation between seaweed diversity and the hydrological parameters was investigated. A significantly negative correlation was recorded between seaweed diversity and Temperature. The hydrological parameters differ with seasonal periods, geographical location, and spatial and temporal variation at selected sites. Temperature is an important factor that was observed to play an important role in controlling seaweed diversity in the present study. The comparative study at Veraval and Sikka coasts gives an idea about the hydrological parameters that determine the water suitability for seaweed population and how it will affect seasonally available seaweed resources.